Industry specialization of private equity firms: a source of buy-out performance heterogeneity. Issue 3 (3rd July 2018) - Le Nadant, Anne-Laure; Perdreau, Frédéric; Bruining, Hans
Abstract: This study sheds new light on the industry specialization of private equity (PE) firms as a source of buy-outs' performance and on the conditions under which these firms can add value to the buy-outs in which they invest. Advantages to specialization are based on specific resources and capabilities that confer the PE funds advantages both in the pre- and post-transaction phases. We argue that the magnitude of the advantages to industry specialization will depend on the criticality of these specific resources for buy-outs' performance improvements. Industry specialization will confer advantages when the target company is weakly or strongly performing before the buy-out because, in that context, performance improvements are more difficult to reach. The analysis is based on a sample of 217 PE-backed buy-outs completed in France between 2001 and 2007. The results show that relative specialization in the industry of the buy-out company results in profit increases of 7.5% greater than buy-outs backed by non-industry-specialized PE firms. Industry specialization also contributes to target company growth, especially when performance improvements are difficult to reach. Besides, the magnitude of the positive industry specialization effect varies between PE firms. This result emphasizes industry specialization as a strategic variable by illustrating heterogeneity in the ability to construct a competitive advantage.